2016
DOI: 10.1371/journal.pone.0150664
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Symptoms: Prevalence, Co-Occurrence and Associations with Self-Perceived Health and Limitations Due To Physical Health – A Danish Population-Based Study

Abstract: A high number of somatic symptoms have been associated with poor health status and increased health care use. Previous studies focused on number of symptoms without considering the specific symptoms. The aim of the study was to investigate 1) the prevalence of 19 somatic symptoms, 2) the associations between the symptoms, and 3) the associations between the somatic symptoms, self-perceived health and limitations due to physical health accounting for the co-occurrence of symptoms. Information on 19 somatic symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…Problems with the assumption were identified by investigating and comparing the bivariate residuals in the three models with the lowest BIC and in the model with a 1-class solution; high residuals indicated violation of the assumption. Based on the bivariate residuals and prior knowledge of associations between symptoms, 8 we decided for which symptoms local dependency should be allowed. Second, to identify the number of classes, the iterative process was reconducted in a model including direct effects between the identified locally dependent symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Problems with the assumption were identified by investigating and comparing the bivariate residuals in the three models with the lowest BIC and in the model with a 1-class solution; high residuals indicated violation of the assumption. Based on the bivariate residuals and prior knowledge of associations between symptoms, 8 we decided for which symptoms local dependency should be allowed. Second, to identify the number of classes, the iterative process was reconducted in a model including direct effects between the identified locally dependent symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…7 However, it can be questioned if this method identifies the persons at the highest risk of poor health and hence leads to blurred or distorted results. 8,9 For example, in a recent study, we found that the associations between symptoms and health status depended on both the specific symptoms and the co-occurrence of symptoms. 8 This emphasized the need for a better and more precise identification of persons at risk for poor health based on their symptom reporting than merely counting symptoms.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations